The Effectiveness of Project-Based Learning Models On Students' Learning Outcomes in Fourth Grade: Animal Metamorphosis Modeling - Dewanti, Frisma Mufti Hafisyah; Nuswantoro, Agung Bangkit; Kurniati, Eva (UIN Sunan Kalijaga Yogyakarta, 2024)
The aim of this study was to address the issue of low student learning outcomes in the Natural Sciences Subject, specifically in the